DNS blocking in KZ: bbc.com, facebook.com, google.com, instagram.com, medium.com +13 more (Kazakhstan) - Voidly (2026)
CRITICAL severity censorship detected in Kazakhstan. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: KZ-2026-0005
Keywords: censorship; KZ; censorship; critical